Effect of β-alanine on humoral immune response in low-dose allergy model - D. B. Chudakov; O. D. Kotsareva; D. S. Tsaregorotseva; E. I. Kashirina; G. V. Fattakhova (Медицинская иммунология, 2021)
At the present time, the efforts of many research groups around the world are aimed at finding new factors triggering the allergic sensitization process linked with IgE synthesis to harmless allergens. According to the recent data, production of tissue cytokines is induced in tissue cells by alarmins, thus, in turn, eliciting pro-allergic immune response. Previously we have shown that β-alanine could be a potential alarmin capable to stimulate production of tissue cytokines. The aim of this work was to determine the impact of β-alanine on humoral immune response in low-dose allergy model. BALB/c mice were immunized by recombinant Asp f 2 protein or commercial ovalbumin (OVA) in the withers 3 times a week with or without β-alanine supplementation. To determine the mechanism of β-alanine effect, α-L-alanine, an isomer which is not MrgD receptor ligand, and β-aminoisobutyrate with β-alanine-like affinity to MrgD ligand, were compared. According to our data, β-alanine stimulated specific IgE and IgG1 production in a short-term course (7 immunizations) and enhanced antibody affinity after long-term (14 immunizations) protocol in the case of low-immunogenic protein Asp f 2. In the case of high-immunogenic OVA protein, the impact of β-alanine was significant only upon antibody affinity. Hence, β-alanine accelerates specific IgE production in the case of low-immunogenic protein. The impact of β-alanine on specific IgE production was not linked to specific MrgD receptor activation, because β-aminoisobutyrate, which is the other ligand of this receptor, did not have a similar effect upon humoral immune response. The effect of β-alanine on IgG1 production seems also independent of MrgD receptor, since the common proteinogenic amino acid α-L-alanine also enhanced specific IgG1 production. The effect of β-alanine on humoral immune response could be linked to its non-specific action, e.g., due to its ability to induce oxidative stress through blocking taurine transporter, or due to its ability to stimulate cellular metabolism.